Tectono-Metamorphic Deformational Features of Dumne area, Hawal Massif, Northeastern Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2025)
The Dumne area forms part of Hawal Massif in the northeastern sector of theNigerian Basement Complex. The region has experienced multiple phases oftectono-metamorphic deformations denoted as D1, D2 and D3 which have playeda significant role in the emplacement of various structural elements and theformation of extensive granitoid bodies. The structural elements are classified intoplastic (foliation and lineation), ductile (fold) and brittle (fractures, faults and joints)respectively. They strike dominantly in the N - S (0 - 20o), NNE - SSW (25 – 35o), NE- SW (45 – 55o) and ENE – WSW (65 – 85o) directions as well as minor E-W (90 –95o) and NW – SE (120 – 150o) directions. The N - S, NNE - SSW and NE - SW are themost dominant and penetrative structures representing a widespread effect of Pan-African orogeny in the area. These structural trends also serve as host to epigeneticvein-type, baryte-fluorite mineralization in the study area. The less dominant ENE -WSW structural trends are pervasive and largely offset in places, suggestive ofstructures that pre-date the Pan-African events.